2021
DOI: 10.3389/fpubh.2021.735151
|View full text |Cite
|
Sign up to set email alerts
|

Aging Immune System and Its Correlation With Liability to Severe Lung Complications

Abstract: Aging is considered to be a decline in physical and physiological events that extensively affect the body's immunity, and is linked with deterioration in both innate and adaptive immune responses. The immune system exhibits profound age-associated variations, known as immunosenescence, comprising a significantly low production of B and T lymphocytes in bone marrow and thymus, a decreased function of mature lymphocytes in secondary lymphoid tissues, a decrease in the synthesis of fresh naïve T cells, and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…times higher number of COVID-19 patients [19]. The correlation between aging and declined innate immunity generally explained the more susceptibility of older persons to infection [20]. Biswas et al (2020) found that male patients with COVID-19 were associated with a significantly increased risk of death by 1.86 times compared to female patients, but we did not study the association between age and gender with the severity of the disease [21].…”
Section: Spearman Correlation Testmentioning
confidence: 89%
“…times higher number of COVID-19 patients [19]. The correlation between aging and declined innate immunity generally explained the more susceptibility of older persons to infection [20]. Biswas et al (2020) found that male patients with COVID-19 were associated with a significantly increased risk of death by 1.86 times compared to female patients, but we did not study the association between age and gender with the severity of the disease [21].…”
Section: Spearman Correlation Testmentioning
confidence: 89%
“…In addition, we found that both recipient and donor age negatively affected B-cell reconstitution. This may indicate that thymic function and bone marrow activity deteriorate with aging, which impairs the production of naïve and mature B cells [34][35][36][37]. However, further studies are needed to elucidate the mechanisms of delayed B-cell immune reconstitution associated with aging.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumonia, an inflammatory lung infection, poses substantial risks for the elderly [ 54 , 55 , 56 ]. Aging weakens the immune system, making older adults more susceptible to severe pneumonia, often resulting in hospitalization and, in severe cases, mortality [ 57 , 58 ]. According to the Centers for Disease Control and Prevention (CDC), about 150,000 adults aged 65+ years are annually hospitalized due to pneumonia in the USA [ 59 ].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%